Rekayasa Alat Pendeteksi Kebocoran Gas Berbasis Arduino Uno Dengan Sensor MQ-2 Pada Regulator LPG - ., Rahmatullah; Umurani, Khairul; Amiruddin, Arfis; Kurniawan, Wahyu; Siregar, Ahmad Marabdi (Rekayasa Material, Manufaktur dan Energi, 2025)
The engineering of an Arduino Uno-based gas leak detection device with an MQ-2 sensor was created to optimize security against gas leaks that occur. The public must know the signs of a leak, such as smelling gas, a hissing sound in the gas line and so on. The aim of engineering this tool is to create an Arduino Uno-based gas leak detection tool that uses the MQ-2 sensor on the LPG regulator. Gas leaks can cause risks such as fire and explosion, so it is important to have a gas detection system. When the sensor detects the presence of gas, the system will trigger a buzzer to provide an audible alarm and turn on the LED light as a visual indicator. The LCD will display the detection status with clear text, namely "Leak Danger" when gas is detected, and "Safe" when there is no leak. The test was carried out using a 3 kg LPG gas cylinder, with the results showing that the MQ-2 sensor could detect gas within 3 seconds. The results of this test prove that the tool developed is able to provide a fast response to gas leaks, so it can be a solution to increase the safety of LPG use.